2008
DOI: 10.1080/14733140801889139
|View full text |Cite
|
Sign up to set email alerts
|

Exploring theatre of the oppressed in family therapy clinical work and supervision

Abstract: Augusto Boal's theatre of the oppressed (TOTO) techniques have been used in education, health, welfare, and prison systems world-wide. However, the link between family therapy clinical supervision and training and TOTO has not been explored, either in Australia or overseas. This innovative action research project explores the ways family therapists and supervisors apply these theatre techniques in their everyday practice. Employing a group-based, cooperative inquiry method, 12 experienced family therapists fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The benefits of experiential learning through the use of the expressive arts include within academic programs: improving self-awareness, developing conceptualization skills, and processing countertransference (Turry, 2001 ). Some other benefits include: self-care and stress reduction (Deaver and Shiflett, 2011 ), an improved supervisory relationship (Scheiby, 2001 ), self-awareness on the part of the student (Austin and Dvorkin, 2001 ), empathic attunement (Cooper, 2001 ), and a sense of empowerment as a future therapist (Proctor et al, 2008 ). For example, Ko ( 2014 ), who examined the experience of six native Korean expressive arts therapy students (four in art therapy and two in dance/movement therapy) in a movement-based program at a Korean university, reported that there was a reduction in perceived authoritarianism paired with an enhancement of verbal sharing with their clinical supervisor.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of experiential learning through the use of the expressive arts include within academic programs: improving self-awareness, developing conceptualization skills, and processing countertransference (Turry, 2001 ). Some other benefits include: self-care and stress reduction (Deaver and Shiflett, 2011 ), an improved supervisory relationship (Scheiby, 2001 ), self-awareness on the part of the student (Austin and Dvorkin, 2001 ), empathic attunement (Cooper, 2001 ), and a sense of empowerment as a future therapist (Proctor et al, 2008 ). For example, Ko ( 2014 ), who examined the experience of six native Korean expressive arts therapy students (four in art therapy and two in dance/movement therapy) in a movement-based program at a Korean university, reported that there was a reduction in perceived authoritarianism paired with an enhancement of verbal sharing with their clinical supervisor.…”
Section: Introductionmentioning
confidence: 99%
“…The final three papers in this issue present varied approaches to qualitative research. A particularly novel action research approach is taken by Proctor, Perlesz, Moloney, McIlwaine, and O'Neill () in studying the application of Theatre of the Oppressed methods (Boal, ) in family therapy clinical work and supervision. Proctor and her colleagues explored ways of teaching family therapists and supervisors to apply these theatre techniques in their everyday practice and documented this process using a group‐based, cooperative inquiry method of action research.…”
mentioning
confidence: 99%